Completeness of chronic disease registration in general practice. - Mant, D; Tulloch, A (1987)
The completeness of chronic disease registration in four general practices was assessed by referring to the Hospital Activity Analysis. Overall, just over half (56%) of the 695 patients who had been discharged from hospital with a diagnosis of diabetes, cancer, myocardial infarction, epilepsy, hypertension, or thyroid disease were identified on the practice disease registers. Patients with diabetes were most likely to be identified (72%), and those who had had a myocardial infarct least likely (43%). If the standard of registration is to be improved general practitioners must be convinced of its value. The Hospital Activity Analysis might be used widely to audit and improve practice registers.